P37 Peroneal muscle activation in chronic ankle instability. (17th September 2017) - O'Shea, N; Flavin, R; Blake, C; Heffernan, E; Persson, U McCarthy
Abstract : Study Design: A case-control study. Background: Throughout existing literature Peroneus Brevis (PB) and Peroneus Longus (PL) are largely coupled and referred to as 'The Peroneals', with few endeavouring to study their individual function. The contribution of PB and PL in the Chronic Ankle Instability (CAI) model remains inconclusive. Objective: Establish whether individuals with CAI, compared with healthy controls, exhibit altered neuromuscular control as demonstrated by surface electromyography (SEMG) for PB, PL and Tibialis Anterior (TA) during a battery of static and dynamic tasks, and Centre of Pressure (COP) data for single-limb balance test with eyes open/closed (SLSEO/SLSEC). Methods and Measures: Eleven adults with CAI and 11 healthy controls performed treadmill walking, jogging, SLSEO/EC, wobble board stance, single-limb calf raise and DVJ. SEMG mean amplitudes were analysed for PB, PL and TA, during all activities except drop vertical jump (DVJ) where muscle onset times were calculated. Mean SEMG was reported as a percentage of Maximum Voluntary Isometric Contraction (MVIC). SLSEO/EC COP data was analysed for both groups. One-way analyses of variance were used to conduct group comparisons. Results: There was significantly lower mean SEMG activity in both PB and PL in the CAI group compared with controls during Calf raise (PB 15.5%, p=0.006, PL 30.3%, p=0.004), a similar trend was noted during SLSEC (PB 24.9%, p=0.003, PL 32.1%, p=0.006), and wobble board activities (PB 16.5%, p=0.04, PL 20.6%, p=0.024). In the CAI group PB also showed significantly reduced activation during SLSEO (12.3%, p=0.003), as did PL during walking (17.8%, p=0.027). There were no statistically significant differences in onset times or COP measures between groups. Conclusion: Participants with CAI demonstrated significantly lower muscle activity of PB and PL compared with healthy controls during dynamic activities. These results may have implications for the focus and content of rehabilitation programs in this cohort.